Partnership working : Policy and practice - Taylor, Marilyn, 1946-; Balloch, Susan (Book collections on Project MUSE., 2001)
This stimulating book analyses experiences of partnerships in different policy fields, identifying the theoretical and practical impediments to making partnership work and critically evaluating the advantages and disadvantages for those involved. Going beyond the confines of statutory partnerships it addresses other important forms of collaboration between voluntary, private and statutory sectors and service users and community and minority groups.